Targeting ferroptosis as a potential prevention and treatment strategy for aging-related diseases - Taiwei Jiao; Yiman Chen; Haiyan Sun; Lina Yang (Elsevier, 2024)
Ferroptosis, an emerging paradigm of programmed cellular necrosis posited in recent years, manifests across a spectrum of maladies with profound implications for human well-being. Numerous investigations substantiate that modulating ferroptosis, whether through inhibition or augmentation, plays a pivotal role in the etiology and control of numerous age-related afflictions, encompassing neurological, circulatory, respiratory, and other disorders. This paper not only summarizes the regulatory mechanisms of ferroptosis, but also discusses the impact of ferroptosis on the biological processes of aging and its role in age-related diseases. Furthermore, it scrutinizes recent therapeutic strides in addressing aging-related conditions through the modulation of ferroptosis. The paper consolidates the existing knowledge on potential applications of ferroptosis-related pharmacotherapies and envisages the translational prospects of ferroptosis-targeted interventions in clinical paradigms.